2014
DOI: 10.1371/journal.pone.0105332
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Profile of Arabidopsis Peroxidases, AtPrx-2, 25 and 71, Contributing to Stem Lignification

Abstract: Lignins are aromatic heteropolymers that arise from oxidative coupling of lignin precursors, including lignin monomers (p-coumaryl, coniferyl, and sinapyl alcohols), oligomers, and polymers. Whereas plant peroxidases have been shown to catalyze oxidative coupling of monolignols, the oxidation activity of well-studied plant peroxidases, such as horseradish peroxidase C (HRP-C) and AtPrx53, are quite low for sinapyl alcohol. This characteristic difference has led to controversy regarding the oxidation mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Consistently, we did not detect significant differences in stem length and weight between wild-type and atprx71 plants, confirming that AtPRX71 has a negligible role in the lignification, at least in this organ. Characterization of AtPRX71 activity in vitro, however, indicates that this protein is able to oxidize 2,6-dimethoxyphenol and syringaldazine, which are model monolignol compounds (Shigeto et al, 2014), suggesting that this PRX may promote polymerization of lignin under specific conditions or in specific tissues. Moreover, AtPRX71 is also able to form protein radicals in vitro (Shigeto et al, 2014); the significantly increased expression of EXT4 observed in 35S:AnPGII plants, therefore, suggests that AtPRX71-mediated extensin cross links may be formed in response to altered CWI to strengthen the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we did not detect significant differences in stem length and weight between wild-type and atprx71 plants, confirming that AtPRX71 has a negligible role in the lignification, at least in this organ. Characterization of AtPRX71 activity in vitro, however, indicates that this protein is able to oxidize 2,6-dimethoxyphenol and syringaldazine, which are model monolignol compounds (Shigeto et al, 2014), suggesting that this PRX may promote polymerization of lignin under specific conditions or in specific tissues. Moreover, AtPRX71 is also able to form protein radicals in vitro (Shigeto et al, 2014); the significantly increased expression of EXT4 observed in 35S:AnPGII plants, therefore, suggests that AtPRX71-mediated extensin cross links may be formed in response to altered CWI to strengthen the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, Shigeto et al () identified peroxidases 2, 25 and 71 as cationic proteins which showed high homology to CWPO‐C from poplar, which also preferred sinapyl alcohol over coniferyl alcohol as substrate (Sasaki et al ). Knock‐out mutants of these three peroxidases showed a decreased lignin content, and although S/G ratio was not lower in mutants than in WT plants (Shigeto et al ), recombinant proteins of AtPrx2 and AtPrx71 were able to oxidize syringyl compounds even more efficiently than guaiacol (Shigeto et al ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, higher oxidation activity for the syringyl unit rather than for the guaiacyl unit was shown in CWPO‐C (Aoyama et al ., ), ZePrx from Z. elegans (GabaldĂłn et al ., ), BPX1 from Betula pendula (Marjamaa et al ., ) and the recombinant proteins AtPrx2 and 71 of A. thaliana . AtPrx2, 25 and 71 were shown to be involved in stem lignification by a reverse genetic study, as described above (see subsection ‘Lignification’), and able to oxidize both guaiacyl and syringyl units (Shigeto et al ., ). CWPO‐C and ZePrx were also suggested to be involved in lignification, because their putative A. thaliana orthologs (AtPrx71 and AtPrx4, 52 and 72, respectively) were shown to be involved in lignification by reverse genetic studies (Herrero et al ., ; FernĂĄndez‐PĂ©rez et al ., , ; Shigeto et al ., ).…”
Section: Biochemical Strategies To Identify Prxs Responsible For Lignmentioning
confidence: 97%
“…CWPO-C and ZePrx were also suggested to be involved in lignification, because their putative A. thaliana orthologs (AtPrx71 and AtPrx4, 52 and 72, respectively) were shown to be involved in lignification by reverse genetic studies (Herrero et al, 2013;Fern andez-P erez et al, 2014Fern andez-P erez et al, , 2015Shigeto et al, 2015). Moreover, CWPO-C, AtPrx2, 25 and 71 can oxidize ferrocytochrome c, suggesting that these Prxs have oxidation activity towards large molecules such as the lignin polymer (Shigeto et al, 2014). CWPO-C can also oxidize a synthetic lignin oligomer (Sasaki et al, 2004).…”
Section: Biochemical Strategies To Identify Prxs Responsible For Lignmentioning
confidence: 99%